EDUKASI TEKNIK MENYUSUI DAPAT MENINGKATKAN KEBERHASILAN LAKTASI PADA IBU POSTPARTUM - Ria Gustirini; Rezah Andriani; Inge Anggi Anggarini (IKesT Muhammadiyah Palembang, 2024)
Introduction : Breastfeeding is a natural process, but in reality not all mothers can breastfeed their babies with the correct technique. Lactation failure caused by improper breastfeeding techniques can have a negative impact on the mother and baby. Research Objective: to analyze the effect of breastfeeding technique education on lactation success. Method: This research is a quasi-experimental research with a one group pretest and posttest design. Sampling was carried out by consecutive sampling Results: The results of the study showed that there was an effect of education on breastfeeding techniques before and after education was provided on the success of lactation in postpartum mothers (p<0.05). Discussion: The role of midwives is really needed in the early weeks postpartum in providing Counseling, Information and Education (KIE) about good and correct breastfeeding techniques.